Factors influencing salivary lactate dehydrogenase levels in oral squamous cell carcinoma and oral potentially malignant disorders - López-Pintor, Rosa María; González-Serrano, José; Vallina, Carmen; Ivaylova Serkedzhieva, Katerina; Virto, Leire; Nuevo, Paula; Caponio, Vito Carlo Alberto; Iniesta, Margarita; Rodríguez Santamarta, Tania; Lequerica Fernández, Paloma; Iglesias Velázquez, Óscar; Hernández, Gonzalo; et al. (Frontiers in Oral Health, 2025)
IntroductionSalivary Lactate Dehydrogenase (sLDH) levels seem to be higher in patients with Oral Squamous Cell Carcinoma (OSCC) and Oral Potentially Malignant Disorders (OPMD) than a control group (CG).MethodsCase-control study. Patients with OPMD [oral leukoplakia (OL) and oral lichen planus (OLP)] and OSCC who attended two services in Spain were selected. sLDH in saliva was measured. Epidemiological, periodontal and specific variables related to OPMD and OSCC were collected.ResultsA total of 92 patients were included: 12 with OSCC, 51 with OPMD (17 OL and 34 OLP), and 29 controls. sLDH values were higher in the OSCC, followed by the OPMD and CG groups, although no significant differences were observed. In the OSCC group, larger tumor size was associated with higher sLDH levels. In the OLP group, sLDH values were higher in patients with symptomatic lesions than in patients with only white lesions, but not significantly. No associations were observed between sLDH and the type of OL (homogeneous vs. non-homogeneous) and the degree of dysplasia. When analyzing periodontal variables among OSCC, OPMD and CG, periodontal probing depth (PPD) and bleeding on probing were significantly higher in the OSCC group, while the plaque index was higher in OPMD patients. The linear regression model for sLDH in the total group identified age and PPD as significant predictors of sLDH levels.DiscussionAlthough sLDH values were higher in OSCC and OPMD patients than in a CG, the results do not support the use of sLDH as a reliable prognostic biomarker of malignancy. Future studies need to consider other factors that may influence sLDH levels, such as age and periodontal status.